Perancangan Jadwal Penggantian dan Persediaan Komponen Mesin Cutting - Trifenaus Prabu Hidayat; Sugioko, Andre; Siagian, Vebryna Shaputri; Kartawidjaya, Maria Angela; Sukwadi, Ronald; Wahju, Marsellinus Bachtiar (Metris: Jurnal Sains dan Teknologi, 2023)
PT. X is a garment industry company that produces clothing products. PT. X has not implemented a maintenance or machine maintenance system. Currently, the company only performs machine maintenance when they are damaged. This causes losses for the company because it can disrupt the smooth running of the production process, such as sudden engine damage, which can cause high machine downtime. Therefore, maintenance of machines is needed in the form of a schedule for replacing and checking cutting machine components with a Preventive maintenance approach to support the production process at the company. In addition to generating replacement schedules and inspecting engine components, Implementing the proposed Preventive maintenance takes the scheduling for maintenance and cleaning of cutting machines. After the replacement schedule and inspection of engine components are generated, it will affect the inventory of engine components. The inventory system proposed is the inventory system model P. Model P is chosen because it is in accordance with the condition of the company and meets the requirements of the model P inventory system. The P inventory system produces a cost of Rp. 22,508,709.